KHITBAH MENURUT PERSPEKTIF HUKUM ISLAM - Novel, Ismail (IAIN Bukittinggi, 2009)
A marriage in Islamic law viewed as a kind of a very lofty agreement (al ‘Aqd alGhalizha). This agreement is regarded as a very important thing inside of a marriage process. Therefore, the agreement needs an introduction related with the process. Generally, in an Islamic literature this introduction called as alkhitbah or asking in marriage. According to Islamic law perspective, there are some norms in the khitbah (asking in marriage) process. One of them is a man forbidden to ask in marriage to a woman as long as the woman is asked in marriage by another man.